ANALISIS EFEKTIVITAS ORGANISASI DARI PERPEKTIF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Suparyanto, Tri (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
This study aims to determine the influence of job satisfaction, Organizational Commitment, and Organizational Climate on Organizational Effectiveness from OCB in PT. Yogyakarta Tugu Televisi. Population and sample in this study is the number of employees of 169 people. Analysis the data used was the validity and reliability test then testing indicator with instrument analysis Path by Smart PLS. From the analysis, the coefficient of determination (R2) noted that OCB was influenced by job satisfaction, organizational commitment and organizational climate by 87% and the remaining 13% was influenced by other factors which not included in the model. Meanwhile, Job Satisfaction significantly effect of 3.540, Organizational Commitment significantly effect of 2.108, Organizational Climate significantly effect of 2.889 and OCB significantly effect of 6.862. From the analysis of the test, the coefficient of determination (R2) noted that the Organizational Effectiveness was influenced by Job Satisfaction, Organizational Commitment, Organizational Climate and OCB by 85%, the rest 15% influenced by other factors not included in the model. Keywords: Job Satisfaction, Organizational Commitment, Organizational Climate, OCB, Organizational Effectiveness